Investigation on mechanical properties and microstructure of coal-based synthetic natural gas slag (CSNGS) geopolymer. (30th October 2020) - Sha, Dong; Pan, Baofeng; Sun, Yiren
Highlights: A novel geopolymer prepared by CSNGS and KOH solution. The pozzolanic activity of CSNGS was evaluated. Effects of curing temperature and activator concentration of geopolymer were studied. The microstructural properties of CSNGS geopolymers were investigated. Abstract: A new geopolymer prepared from a coal-based synthetic natural gas slag (CSNGS) and an alkali activator of potassium hydroxide (KOH) solution was studied. Firstly, the pozzolanic activity of CSNGS was evaluated. Then, the CSNGS geopolymers were produced under different conditions, and its compressive strength was also analyzed. Finally, XRD, FESEM/EDS, and FT-IR were carried out to investigate the microstructural properties and the reaction mechanism of CSNGS geopolymers. The findings showed that the CSNGS with a reasonable milling time exhibited high pozzolanic activity, and the composite pozzolanic activity index (CPAI) was the highest (CPAI = 92.2%) when the milling time was 45 min. Also, high heat curing temperature, long heat curing time and appropriate activator concentration were beneficial for the development of geopolymers strength. For CSNGS geopolymers, a maximum compressive strength of 27.8 MPa at 28 days was obtained. In addition, the XRD presented that the CSNGS geopolymers had an amorphous phase. The FESEM showed that a highly denser microstructure was formed by a number of geopolymeric gels attributing to the optimal synthesis conditions. The EDS analysis illustrated that the K-A-S-H gel was generated during the geopolymerization. The FT-IR suggested that the carbonization was easy to produce due to the excessive alkalinity. In general, it was feasible to fabricate geopolymers with the CSNGS and KOH solution.